Kepadatan Populasi Cacing Tanah (Haplotaxida: Lumbricina) Sebagai Bioindikator Kesuburan Tanah Di Kebun Nusantara PT. Cinquer Agro Nusantara - Lisana Husna Imaniar; Lily Arseliana; Gres Maretta; Andy Darmawan; Winati Nurhayu; Dian Anggria Sari; Muhammad Zulhiyadi Nanda (Program of Biology Education, Universitas Lambung Mangkurat, 2023)
Earthworms (Haplotaxida: Lumbricina) are bioindicators of soil fertility. Agricultural systems applied to an agricultural area can affect the presence of earthworms there. This study aims to determine the density of earthworms in plantations owned by PT. Cinquer Agro Nusantara with Agroforestry-Organic, Monoculture-Semiorganic, Polyculture-Organic, Monoculture-Organic, and farmer-owned plantations with Monoculture-Inorganic system. The plot is determined with line transect method and samples of earthworms are taken with hand sorting method. Data analysis was carried out with ANOVA and Post Hoc T-Test with Bonferroni correction. The results showed that the density of earthworms in pepper plantations with Agroforestry-Organic, Monoculture-Semi-organic, Polyculture-Organic, and Monoculture-Organic farming systems is significantly greater than pepper plantations with Monoculture-Inorganic farming system.